Radiological protection and certification for medical professionals in Brazil - CAMILLE Pinho Vieira DE CASTRO DA LUZ; Lidia Vasconcelos de Sá; José Ubiratan Delgado (Brazilian Journal of Radiation Sciences, 2018)
Radiation protection is supported by three pillars: justification, optimization and dose limitation. The safe use of ionizing radiation is governed by the limits of public and occupational exposure, justification and optimization for medical exposures. In Brazil there are at least 200,000 professionals working in medical facilities that involve the use of ionizing radiation. There are standards in radiation protection that establish the obligation of the performance of certified professionals in the facilities through pre-established criteria. The certification in radiation protection assesses the skills, knowledge and competence of the professionals. A survey, classification and detailed analysis of the mandatory requirements by the regulatory body for professional performance in this area were carried out as well as the competencies and skills required in the radiation protection standards in force in the country. The results obtained in this evaluation demonstrated that the certification process of these professionals aims at higher quality and optimization of the medicals procedures performed. The direct beneficiaries of this process would be the practitioners themselves and patients of medical practices involving the use of ionizing radiations. Certifying medical professionals in radiation protection would meet the demand of national standards that require a quality control of those involved in medical treatments using ionizing radiations.